Entrepreneurial Readiness in Community-Based Herbal Education - Adi, Yakobus Saktono (Green Publisher, 2026)
This study examines the influence of growth mindset, innovation, learning motivation, and social and environmental support on entrepreneurial readiness among participants of the Herbal Medicine Class (HMC) organized by Sekar Utami Toga MSME, a community-based herbal learning initiative in Tangerang Selatan, Banten. Using a quantitative associative design, data were collected through a Likert-scale questionnaire from 58 participants and analyzed using correlation and multiple regression techniques. The results reveal growth mindset and innovation significantly and positively affect entrepreneurial readiness, whereas learning motivation and social and environmental support show positive but nonsignificant effects. The model explains 54% of the variance in entrepreneurial readiness (R²=0.540), indicating that psychological and behavioral factors play dominant role than contextual ones in influencing entrepreneurial preparedness. Participants with strong growth mindsets show greater confidence, adaptability, and initiative, while innovative learners display creativity and problem-solving skills that enhance entrepreneurial capacity. Motivation and social support boost engagement but influence entrepreneurship indirectly through internal readiness and available opportunities. Overall, the study highlights community-based herbal learning as a medium for developing growth-oriented mindsets, creativity, and self-reliance. The integration of experiential, reflective, and innovation-focused learning to strengthen entrepreneurial outcomes and community education as a catalyst for sustainable local empowerment.